Infostorms Why do we 'like'? Explaining individual behavior on the social net. - Hendricks, Vincent F.; Hansen, Pelle G.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
The information society is upon us. New technologies have given us back pocket libraries, online discussion forums, blogs, crowdbased opinion aggregators, social media and breaking news wherever, whenever. But are we more enlightened and rational because of it? With points of departure in philosophy, logic, social psychology, economics, and choice and game theory, Infostorms shows how information may be used to improve the quality of personal decisions and group thinking but also warns against the informatonal pitfalls which modern information technology may amplify: From science to reality culture and what it really is, that makes you buy a book like this. "With this brilliant book, we have been warned. It is up to all of us in the world today to be stewards of the common resource that is trustworthy and relevant information". Adam Brandenburger, Stern School of Business, NYU "It is a highly recommended read for social scientists and concerned citizens alike". Christian List, London School of Economic.
Chapter 1: Off We Go -- Part 1: How Information Technologies May Amplify Irrational Group Behavoir -- Chapter 2: Common Knowledge and Public Space -- Chapter 3: Pluralistic Ignorance and Bystanders -- Chapter 4: Informational Cascades and Lemmings -- Part Ii: Why Free Choice, Markets and Deliberation Cannot Protect Us -- Chapter 5: Choice: Framing Choice -- Chapter 6: Markets: Choosing Frames -- Chapter 7: Deliberation: Polarized People -- Chapter 8: The Constitutive Games We Play -- Part 3: Wars, Bubbles and Democracy -- Chapter 9: Wars -- Chapter 10: Bubbles -- Chapter 11: Democracy -- Part 4: Postscript: The Social Power Of Information Architecture -- Chapter 12: The Social Powers of Infostorms.
Keywords: Psychology; Philosophy; Popular Science in Psychology